2021
DOI: 10.4314/wiojms.si2021.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The residual circulation profile of the Bons Sinais Estuary in central Mozambique - potential implications for larval dispersal and fisheries

Abstract: The residual circulation in estuaries determines the net exchange of water, heat, salt, fine sediments and drifting biological organisms between estuarine and nearshore marine waters. The Bons Sinais Estuary in central Mozambique is ~ 30 km long with the city of Quelimane and an industrial port on the northern bank of its upper reaches. To investigate residual circulation in the estuary, seasonal (wet, dry and transition season) CTD profiling data were collected at 11 fixed stations between the upper estuary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…On the other hand, in the upper estuary, salinity averages of less than 5 were still recorded in the first months of the dry season, namely, May to June. A previous study found similar results [54] in the BSE by noting strong spatial gradients and seasonal variations in salinity, and concluded that the estuary is river-dominated during the wet season and sea-tide-dominated during the dry season.…”
Section: Environmental Parameterssupporting
confidence: 74%
See 3 more Smart Citations
“…On the other hand, in the upper estuary, salinity averages of less than 5 were still recorded in the first months of the dry season, namely, May to June. A previous study found similar results [54] in the BSE by noting strong spatial gradients and seasonal variations in salinity, and concluded that the estuary is river-dominated during the wet season and sea-tide-dominated during the dry season.…”
Section: Environmental Parameterssupporting
confidence: 74%
“…According to the critical swimming speed (CSS) of some larval fish families, currents in estuaries are somewhat stronger and stifle the ingress and retention of larvae. For instance, the CSS of 18.7 cm/s for Clupeidae [108], CSS of 18.4 cm/s for Blennidae [108], and CSS of 22.1 cm/s Scianidae [109] are lower than the maximum currents in the estuary of around 100 cm/s determined by [54] at spring tides. Under such severe hydrodynamic conditions, some species may use different strategies to be retained in the estuary, including short-range directional horizontal swimming against the axial currents, vertical migration, and the use of residual upstream flows, especially over shallower areas [29].…”
Section: Larval Taxa Composition Abundance Distribution and Developme...mentioning
confidence: 81%
See 2 more Smart Citations